Impact of economic freedom on corruption revisited in ASEAN countries: A Bayesian hierarchical mixed-effects analysis - Nguyen Ngoc Thach; Bui Hoang Ngoc (Economies, 2021)
Conceptual and applied studies assessing the linkage between economic freedom and corruption expect that economic freedom boosts economic growth, improves income, and reduces levels of corruption. However, most of them have concentrated on developed and developing groups, while the Association of Southeast Asian Nations (ASEAN) countries have drawn much less attention. Empirical findings are most often conflicting. Moreover, previous studies performed rather simple frequentist techniques regressing one or some freedom indices on corruption that do not allow for grasping all the aspects of economic freedom as well as capturing variations across countries. The study aims to investigate the effects of ten components of economic freedom index on the level of corruption in ten ASEAN countries from 1999 to 2018. By applying a Bayesian hierarchical mixed-effects regression via a Monte Carlo technique combined with the Gibbs sampler, the obtained results suggest several findings as follows: (i) In view of probability, the predictors property rights, government integrity, tax burden, business freedom, labor freedom, and investment freedom have a strongly positive impact on the response perceived corruption index; (ii) Government spending, trade freedom, and financial freedom exert a strongly negative effect, while the influence of monetary freedom is ambiguous; and (iii) There is an existence of not only random intercepts but also random coefficients at the country level impacting the model outcome. The empirical outcome could be of major importance for more efficient corruption controlling in emerging countries, including ASEAN nations.
Keywords: C11; C33; D14; H31; H51; I13; 330; ASEAN countries; Bayesian hierarchical mixed-effects regression; corruption; economic freedom; economic growth